Volume 6: Turbomachinery, Parts a and B 2006
DOI: 10.1115/gt2006-90040
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Unsteady CFD Model of Compressor Stability

Abstract: A three-dimensional unsteady CFD code called CSTALL has been developed and used to investigate compressor stability. The code solved the Euler equations through the entire annulus and all blade rows. Blade row turning, losses, and deviation were modeled using body force terms which required input data at stations between blade rows. The input data was calculated using a separate Navier-Stokes turbomachinery analysis code run at one operating point near stall, and was scaled to other operating points using over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Spakovszky et al [7] attempted to stabilize rotating stall and studied stall inception pattern in a single-stage transonic compressor with radial inlet distortion using active feedback control. Chima [8] has computationally studied the performance of NASA stage 35 using a 3D unsteady code and found that the performance agreed well with the experimental results with radial distortion and shows reduction in the stable flow range of the compressor. Yang and Gu [9] have conducted experimental and computational investigations to evaluate the effects of radially distorted incident flow on the performance of an axial flow fan with three kinds of forwarded-skewed blades.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Spakovszky et al [7] attempted to stabilize rotating stall and studied stall inception pattern in a single-stage transonic compressor with radial inlet distortion using active feedback control. Chima [8] has computationally studied the performance of NASA stage 35 using a 3D unsteady code and found that the performance agreed well with the experimental results with radial distortion and shows reduction in the stable flow range of the compressor. Yang and Gu [9] have conducted experimental and computational investigations to evaluate the effects of radially distorted incident flow on the performance of an axial flow fan with three kinds of forwarded-skewed blades.…”
Section: Introductionmentioning
confidence: 50%
“…Many of the recent experimental and numerical studies have focused on studying the effect of different inlet total pressure distortion on the overall performance of a compressor/fan [7,8] to achieve improvement in the performance and distortion insensitive rotors. Spakovszky et al [7] attempted to stabilize rotating stall and studied stall inception pattern in a single-stage transonic compressor with radial inlet distortion using active feedback control.…”
Section: Introductionmentioning
confidence: 99%
“…In Gong's model, components of the body force for the flow loss F p are modeled by increases as the mass flow rate (MFR) increases for a fixed rotor speed. However, Chima 10 showed that entropy production across a blade zone decreases as MFR increases from a near-surge to a near-choking condition, and entropy production is directly connected to F p as…”
Section: B Body Force Modelmentioning
confidence: 99%
“…9 A direct coupling of the inlet and full-annulus fan blades in the computational domain would give a more realistic simulation of the inlet-fan interaction, but the computational cost would be prohibitively large, especially for shape-design applications, in which more than tens of flow simulations are usually required. The body force approach [9][10][11][12] has been drawing attention as an alternative to simulating the coupling with full-annulus fan blades. This approach uses body force terms to model flow turning and loss due to rotor/stator blade rows.…”
mentioning
confidence: 99%
“…The flow range for the application of the time lag equations is shown in Figure 2. A throttle is imposed at the outlet according to [19] …”
Section: Transient Simulationsmentioning
confidence: 99%